Examining the Effectiveness of Relationship Marketing Strategies on Medical Tourism - Lai, H.; Chen, P.; Lin, Chad (Atlantis Press, 2016)
Medical tourism is one of the fastest-growing industries in the world as many patients are looking to access healthcare services that are not available to them in their home countries. Many hospitals and healthcare centers are now offering numerous products and services in order to fully reap the benefits from it. However, little research which examines the effects of relationship marketing on the medical tourism exists. Hence, the aims of this study are to: (1) examine the relationship between the relationship marketing strategies and the medical tourism industry; and (2) help medical tourism operators to identify some of the key issues that exist within the industry. In-depth interviews were conducted with ten senior Taiwanese tour guides who had extensive experience in dealing with the medical tourism industry. The results indicate that relationship marketing was one of the crucial factors which had an impact on the willingness of tour guides to make necessary travel arrangements for medical tourists. The environment of health examination center, the ability of its doctors to diagnose a patient’s condition, and the professional image of its doctors could also affect the effectiveness of the relationship marketing on medical tourism as well as the efforts in arranging a follow-up visit to the health examination center. The findings can provide senior executives of health examination centers and travel agencies with a more realistic insight in dealing with issues and challenges arising from the medical tourism.